Infection-induced thrombin production: a potential novel mechanism for preterm premature rupture of membranes (PPROM) - Feng, Liping; Allen, Terrence K.; Marinello, William P.; Murtha, Amy P. (American journal of obstetrics and gynecology, 2018)
Preterm premature rupture of membranes is a leading contributor to maternal and neonatal morbidity and death. Epidemiologic and experimental studies have demonstrated that thrombin causes fetal membrane weakening and subsequently preterm premature rupture of membranes. Although blood is suspected to be the likely source of thrombin in fetal membranes and amniotic fluid of patients with preterm premature rupture of membranes, this has not been proved. Ureaplasma parvum is emerging as a pathogen involved in prematurity, which includes preterm premature rupture of membranes; however, until now, prothrombin production that has been induced directly by bacteria in fetal membranes has not been described. This study was designed to investigate whether Ureaplasma parvum exposure can induce prothrombin production in fetal membranes cells. Primary fetal membrane cells (amnion epithelial, chorion trophoblast, and decidua stromal) or full-thickness fetal membrane tissue explants from elective, term, uncomplicated cesarean deliveries were harvested. Cells or tissue explants were infected with live Ureaplasma parvum (1×105, 1×106 or 1×107 colony-forming units per milliliter) or lipopolysaccharide (Escherichia coli J5, L-5014; Sigma Chemical Company, St. Louis, MO; 100 ng/mL or 1000 ng/mL) for 24 hours. Tissue explants were fixed for immunohistochemistry staining of thrombin/prothrombin. Fetal membrane cells were fixed for confocal immunofluorescent staining of the biomarkers of fetal membrane cell types and thrombin/prothrombin. Protein and messenger RNA were harvested from the cells and tissue explants for Western blot or quantitative reverse transcription polymerase chain reaction to quantify thrombin/prothrombin protein or messenger RNA production, respectively. Data are presented as mean values ± standard errors of mean. Data were analyzed using 1-way analysis of variance with post hoc Dunnett’s test. Prothrombin production and localization were confirmed by Western blot and immunostainings in all primary fetal membrane cells and tissue explants. Immunofluorescence observations revealed a perinuclear localization of prothrombin in amnion epithelial cells. Localization of prothrombin in chorion and decidua cells was perinuclear and cytoplasmic. Prothrombin messenger RNA and protein expression in fetal membranes were increased significantly by Ureaplasma parvum, but not lipopolysaccharide, treatments in a dose-dependent manner. Specifically, Ureaplasma parvum at a dose of 1×107 colony-forming units/mL significantly increased both prothrombin messenger RNA (fold changes in amnion: 4.1±1.9; chorion: 5.7±4.2; decidua: 10.0±5.4; fetal membrane: 9.2±3.0) and protein expression (fold changes in amnion: 138.0±44.0; chorion: 139.6±15.1; decidua: 56.9±29.1; fetal membrane: 133.1±40.0) compared with untreated control subjects. Ureaplasma parvum at a dose of 1×106 colony-forming units/mL significantly up-regulated prothrombin protein expression in chorion cells (fold change: 54.9±5.3) and prothrombin messenger RNA expression in decidua cells (fold change: 4.4±1.9). Our results demonstrate that prothrombin can be produced directly by fetal membrane amnion, chorion, and decidua cells. Further, prothrombin production can be stimulated by Ureaplasma parvum exposure in fetal membranes. These findings represent a potential novel underlying mechanism of Ureaplasma parvum–induced rupture of fetal membranes.